The impact of assurance on compliance management systems on bank directors' decisions - Reiner Quick; Sanjar Sayar (International Journal of Auditing, 2020)
Numerous corporate scandals, in conjunction with managerial misbehavior, demonstrate the need for compliance management systems (CMS) and the relevance of CMS assurance. This study investigates the impact of CMS assurance on German bank directors' perceptions and decisions, and analyzes whether the type of assurer and the level of provided assurance are relevant. For this purpose, we conducted an experiment with 105 bank directors and used ANOVA to analyze their reliance on the hypothetical company's CMS, and their decisions regarding credit granting, purchase, and recommendation of shares. We chose a 2 2 + 1 between-subjects design, manipulating the assurance provider (audit firm vs. third party) and the level of assurance (limited vs. reasonable), and adding a control condition without any assurance. Our results suggest that assured CMS positively affect bank directors' perceptions and decisions, compared to CMS without assurance. Furthermore, we find that our perception measure and all three of our decision measures are strongly associated with the choice of assurance provider, but only two decision measures are associated with the assurance level. Bank directors prefer assurance provision by an audit firm, whereas the findings regarding the impact of the assurance level are inconclusive. The study's results, which confirm the decision-usefulness of CMS assurance, are of interest for managers, in particular compliance officers, auditors, creditors, regulators, and academics.
Keywords: 650; Assurance level; assurance services; bank directors; Compliance Management System; compliance-assurance